MP35: The CanadiEM Junior Editor Program: Integrating medical students and junior residents into a dedicated FOAMed training program. (15th May 2017) - Bravo, M.; Carey, R.; Nguyen-Dinh, D.; Chan, T.M.; Thoma, B.
Abstract : Introduction/Innovation Concept: Free Open Access Medical education (FOAM) is a rapidly emerging medium for the dissemination of medical knowledge, especially in Emergency Medicine. However, the most contributors to FOAM are EM attendings who write on established platforms which they also maintain. EM learners have difficulty breaking into this quickly evolving field. In an effort to encourage FOAM involvement of trainees early in their careers, CanadiEM recruited 10 junior residents and medical students with the purpose of developing the skills necessary to contribute to FOAM. These Junior Editors actively participate in the blog workflow, developing writing, editorial, and management skills necessary to operate a high-traffic EM website.Methods: Potential candidates were recruited by placing an advertisement and application on the CanadiEM website. 10 medical students or junior residents were invited to online group video interviews and were all accepted as Junior Editors (JE). Senior CanadiEM staff held online training sessions for all new JEs on how to use Wordpress to create, edit and publish posts, as well as basics in Search Engine Optimization. The junior editors collaboratively developed an instructional document containing the information they learned during these sessions. JEs then volunteered for editorial jobs via an online messaging system (Slack) as they became available. After uploading the draft of each post, the final products are reviewed by senior Editor and feedback was given to each JE.Curriculum, Tool, or Material: All JEs have learned to use the Wordpress blogging platform to create, edit, and upload posts; optimize blog posts for search engines. Following their own interests, some JEs have also learned to edit podcasts, promote the blog on social media resources (Twitter and Facebook), create infographics, and copy-edit blog posts.Conclusion: After 8 months, the JE program has yielded 6 very active editors who maintain a strong blog workflow, have well-developed social media skills, and are actively involved in developing their own content for future posts. The JE program is a strong pathway to introduce medical trainees to both the technical and creative aspects of FOAM and serves as a novel approach to transition students from passive utilization of online content to active contributors.